Cosmopolitan Love Utopian Vision in D. H. Lawrence and Eileen Chang - Yao, Sijia (University of Michigan Press, 2023)
Love, and the different manifestations of it, is a common theme in literature around the world. In Cosmopolitan Love, Sijia Yao examines the writings of D. H. Lawrence, a British writer whose literature focused primarily on interpersonal relationships in domestic settings, and Eileen Chang, a Chinese writer who migrated to the United States and explored Chinese heterosexual love in her writing. While comparing the writings of a Chinese writer and an English one, Yao avoids a direct comparison between East and West that could further enforce binaries. Instead, she uses the comparison to develop an idea of cosmopolitanism that shows how the writers are in conversation with their own culture and with each other. Both D. H. Lawrence and Eileen Chang wrote stories that are influenced by-but sometimes stand in opposition to-their own cultures. They offer alternative understandings of societies dealing with modernism and cultural globalization. Their stories deal with emotional pain caused by the restrictions of local politics and economics and address common themes of incestuous love, sexual love, adulterous love, and utopian love. By analyzing their writing, Yao demonstrates that the concept of love as a social and political force can cross cultural boundaries and traditions to become a basis for human meaning, the key to a cosmopolitan vision.